Accelerated partial breast irradiation—Redefining the treatment target for women with early stage breast cancer. Issue 3 (4th April 2019) - Shah, Chirag; Vicini, Frank
Abstract: Following breast conserving surgery, the standard of care has been to deliver adjuvant radiation therapy directed to the whole breast (WBI) over a period of 3‐7 weeks. Over the past decade, increasing data have supported the concept that treatment to the whole breast may not be required in selected patients, allowing for the emergence of partial breast irradiation (PBI). Multiple randomized trials with 5‐10 years of follow‐up have been published documenting the safety and efficacy associated with PBI using multiple techniques. Questions that remain to be answered include (a) what is the optimal PBI technique for each clinical scenario, (b) are there additional patients that can be effectively managed with PBI approaches, and (c) are there different techniques/dose schedules that allow for further reduction in treatment duration and/or toxicities? Partial breast irradiation represents a standard approach for appropriately selected patients. PBI provides comparable clinical outcomes to WBI while allowing for a reduction in the duration treatment and the potential for reduced toxicities. Future studies may also help to better define which patients require no radiation, PBI, hypofractionated WBI or conventional WBI, based upon patient, clinical, pathologic features as well as potentially using tumor genetics.